Professional Competence of Teachers on Thematic Learning in Elementary Education - Aldi Nurdiansyah; Vera Yuli Erviana; Nhelbourne Mohammad (International Journal of Learning Reformation in Elementary Education, 2023)
Online thematic learning requires creative teachers to prepare practical learning experiences for students, choose basic competence from various learning subjects and arrange them so that learning becomes more meaningful, engaging, and fun. This study aims to analyze the professional competence of teachers in thematic learning at elementary schools. This research is a type of qualitative research with a descriptive approach. The validity of the data in this study uses triangulation techniques and sources. Data collection techniques use interviews, observation and documentation methods. The research subjects were the principal, lower, and upper-grade  teachers. The data analysis techniques used are techniques by Miles and Huberman. The results showed that the professional competence of elementary school teachers in thematic learning is an indicator that is applied, namely the understanding of material, structure, concepts, and scientific mindsets. The subjects are online thematic implementation, mastering basic competency standards, developing learning materials creatively, creating professionalism on an ongoing basis, and mastering information and communication technology have been carried out well with evidence from research data. Thus, teachers already have professional competence in elementary school in thematic learning.